A novel welfare and scientific approach to conducting dog metabolism studies allowing dogs to be pair housed. (December 2020) - Kendrick, John; Stow, Ruth; Ibbotson, Neil; Adjin-Tettey, Georgina; Murphy, Beverley; Bailey, Glynn; Miller, James; Helleberg, Hans; Finderup Grove, Mette; Øvlisen, Kirstine; Hansen, Jesper Juhl
Metabolism cages are designed to conduct absorption, distribution, metabolism and excretion (ADME) studies, enabling an 'excretion balance' scientific objective to be met. Historically, the design of dog metabolism cages has involved single housing. This type of housing has limitations for normal social behaviours and has been largely unchanged for 25–30 years. Improving animal welfare is a focus area for the authorities as well as the industry throughout the European Union. A collaboration was developed between Novo Nordisk and Covance to enhance the design of metabolism cages, allowing dogs to be pair housed. The purpose of the study was to compare excretion balance data from pair-housed and singly housed dogs in order to demonstrate that conducting excretion balance studies with a pair-housing design improves animal welfare without compromising the scientific integrity of the study. A radiolabelled test compound, [ 14 C]-Quetiapine, was selected for this investigation based on its excretion profile. The assessment of the dogs' stress levels was investigated by measuring the levels of serum cortisol as an indicative biomarker. Results were inconclusive due to large variations in cortisol levels. However, dogs appeared calmer in the pair-housing setting. The overall mean recovery (±standard deviation) for pair-housed animals (94.0 ± 0.66% of the dose) was equivalent to that from singly housed dogs (93.0 ± 2.29%). Based on these data, we conclude that pair housing of dogs for future metabolism ADME studies does not compromise the scientific integrity, and therefore is a major progression in the design of these studies, enhancing welfare.